Cross-Cultural Marketing Communication: A Comparative Analysis of Strategies in Global Campaigns - Dr. Mohammed Samiuddin Sahem (International Journal of Engineering and Management Research, 2023)
Due to the advent of globalisation, the establishment of global markets has led to a notable increase in the number of enterprises operating across many nations. The emergence of multicultural organisations may be attributed to companies' efforts to extend their operations outside conventional geographical boundaries. Within these firms, individuals from many nationalities interact with one another in order to accomplish the objectives of the company. The attraction and profitability of these expansions for enterprises may be evident; yet, the operational and managerial challenges associated with global firms are more complex compared to local ones. The global business landscape is shaped by a multitude of factors, including divergences in social, cultural, economic, legal, and political contexts. Engaging in global commercial operations exposes organisations to a range of potential risks, such as political risk, currency risk, and cultural risk, among others. Human resources play a vital role in facilitating the smooth running of company divisions, both at local and worldwide levels. The objective of this research is to examine the challenges associated with cross-cultural marketing faced by organisations engaged in global marketing endeavors. The research highlights the significance of possessing a comprehensive comprehension of a foreign culture, demonstrating respect towards a foreign culture, and implementing management practices that are appropriately attuned to cultural variations. These factors are identified as crucial in enabling a company to effectively address the challenges associated with cross-cultural marketing.